Iodine deficiency in pregnant women after the adoption of the new provincial standard for salt iodization in Zhejiang Province, China - Guangming Mao; Wenming Zhu; Zhe Mo; Yuanyang Wang; Xiaofeng Wang; Xiaoming Lou; Zhifang Wang (BMC, 2018)
Abstract Background Zhejiang has achieved the goal of elimination of iodine deficiency disorders (IDD) via the implementation of universal salt iodization (USI) since 2011. Iodine content in household table salt decreased from the national standard (35 ppm) to the Zhejiang provincial standard (25 ppm) in 2012. It is crucial to periodically monitor iodine status in pregnant women because IDD in pregnancy have adverse effects on fetal neurodevelopment. Methods We carried out a cross-sectional study between April 2014 and September 2015 in the eight sentinel surveillance counties across Zhejiang Province, where IDD was previously known to be endemic. A total of 1304 pregnant women participated and provided a random spot urine sample and a household table salt sample. Urinary iodine concentration (UIC) was determined using arsenic-cerium catalytic spectrophotometry. Iodine content in salt was measured using a titration method with sodium thiosulphate. Results Overall, the median UIC of the total study population of pregnant women was 129.3 μg/L, with a higher UIC in inland (152.54 μg/L) and a lower UIC in coastal counties (107.54 μg/L). Household coverage of iodized salt was 94.6% and the rate of adequately iodized salt was 89.9%. Conclusions Our results indicate deficient iodine status in the pregnant population of Zhejiang, according to the lower cut-off value of optimal iodine nutrition (150 μg/L) recommended by the World Health Organization. In addition to sustaining USI, more efforts are urgently needed to improve iodine intake in women during pregnancy, especially those residing in the coastal counties.